Intensive care medicine MCQs multiple choice questions with explanatory answers - Abbas, Shoneen; Herod, Ruth; Horner, Daniel (Tfm Pub., 2015)
This book contains 270 multiple-choice questions allowing self-assessment of the breadth of knowledge required of the modern intensivist. The book is divided into three papers each consisting of 60 multiple true false (MTF) and 30 single best answer (SBA) questions covering areas including resuscitation, diagnosis, disease management, organ support, and ethical and legal aspects of practice. The MTF questions test factual knowledge and understanding of the evidence base underpinning intensive care medicine, while the SBA questions test the ability of the candidate to prioritise, compete options and make the best decision for the patient. Each question is peer reviewed and accompanied by concise and detailed explanatory notes with references to guide further reading. All the authors are practising intensive care physicians with firsthand experience of professional examinations in the specialty.